UNLOCKING THE QRIS IMPACT: AN ANALYSIS OF MOBILE PAYMENT AMONG MSMEs USING TECHNOLOGY ACCEPTANCE MODEL (TAM) - Lolowang, Tirza; Tasik, Hizkia H. D.; Gunawan, Emilia M. (Universitas Sam Ratulangi, 2024)
The rapid digitalization of Indonesia’s payment systems has introduced QRIS (Quick Response Code Indonesian Standard) to facilitate cashless transactions among Micro, Small, and Medium Enterprises (MSMEs). This study investigates QRIS acceptance among MSMEs in Manado, North Sulawesi, using the Technology Acceptance Model (TAM). Key factors: perceived usefulness, perceived ease of use, and attitude toward use, were analyzed for their impact on behavioral intention to adopt QRIS. Data from 100 MSMEs was analyzed with STATA 17 and SmartPLS 4 software. Findings reveal that perceived usefulness significantly influences attitude (path coefficient = 0.642, t-statistic = 5.832, p-value = 0.000), while perceived ease of use has a strong positive impact on attitude (path coefficient = 0.944, t-statistic = 105.206). The influence of perceived ease of use on perceived usefulness is weaker, suggesting external factors like experience and accessibility may affect this relationship. Attitude toward use significantly shapes the intention to adopt QRIS (path coefficient = 0.857, t-statistic = 33.542). The study underscores the role of user-friendly solutions in enhancing digital financial inclusion among MSMEs. Future research should consider factors like social influence and trust to deepen understanding of technology adoption across diverse users. This research contributes to mobile payment studies in developing economies, offering insights for policymakers and practitioners supporting MSME digitalization.